Positive Art: Artistic Expression and Appreciation as an Exemplary Vehicle for Flourishing. Issue 2 (June 2016) - Lomas, Tim
The relevance of the arts to well-being has been recognized within clinical fields, as reflected in therapeutic forms based on various art modalities, from music to drama therapy. However, there has hitherto been little appreciation of the broader potential of the arts as a vehicle for flourishing and fulfillment in fields such as positive psychology. As such, this article proposes the creation of "positive art" as a field encompassing theory and research concerning the well-being value of art. To show the scope and possibilities of this proposed field, the article provides an indicative summary of literature pertaining to 4 major art forms: visual art, music, literature, and drama. Moreover, the article identifies 5 main positive outcomes that are consistently found in the literature across all these forms: sense-making, enriching experience, aesthetic appreciation, entertainment, and bonding. The article aims to encourage a greater focus on the arts in fields such as positive psychology, enabling science to more fully understand and appreciate the positive power of the arts.